Slow oscillations in the mouse hippocampus entrained by nasal respiration - Yanovsky, Yevgenij; Ciatipis, Mareva; Draguhn, Andreas; Tort, Adriano B. L.; Brankačk, Jurij (The journal of neuroscience, 2014)
Different types of network oscillations occur in different behavioral, cognitive, or vigilance states. The rodent hippocampus expresses prominent θ oscillations at frequencies between 4 and 12 Hz, which are superimposed by phase-coupled γ oscillations (30-100 Hz). These patterns entrain multineuronal activity over large distances and have been implicated in sensory information processing and memory formation. Here we report a new type of oscillation at near-θ frequencies (2-4 Hz) in the hippocampus of urethane-anesthetized mice.
Gesehen am 29.09.2020